2022
DOI: 10.1111/jjns.12486
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of nurse‐initiated sedation management in an intensive care unit: A two‐phase prospective study in Japan

Abstract: This study aimed to evaluate whether nurse-initiated sedation management could provide more appropriate sedation compared to usual care in a Japanese intensive care unit (ICU). Methods: We conducted a single-center, prospective observational study before and after implementing nurse-initiated sedation using instruction sheets. Patients who had been admitted to a general adult ICU were enrolled.Before our ICU started nurse-initiated sedation (pre-implementation care), adjustment of sedatives and analgesics was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It has been reported that non-compliance of the ABCDEF bundle significantly inhibits the implementation of ET in ICU [ 124 ], directly resulting in poor outcomes [ 125 ]. Optimised sedation and pain control [ 126 ] and delirium management [ 127 ] are essential for the successful implementation of ET. Furthermore, family involvement in ET has potential benefits of emotional support and improved motivation for ICU patients [ 128 ].…”
Section: How To Maximise and Enhance The Effect Of Exercise Therapymentioning
confidence: 99%
“…It has been reported that non-compliance of the ABCDEF bundle significantly inhibits the implementation of ET in ICU [ 124 ], directly resulting in poor outcomes [ 125 ]. Optimised sedation and pain control [ 126 ] and delirium management [ 127 ] are essential for the successful implementation of ET. Furthermore, family involvement in ET has potential benefits of emotional support and improved motivation for ICU patients [ 128 ].…”
Section: How To Maximise and Enhance The Effect Of Exercise Therapymentioning
confidence: 99%